Equilibrium Vengeance - Daniel Friedman; Nirvikar Singh (Center for Economic Studies and ifo Institute (CESifo), 2002)
This paper introduces two ideas, emotional state dependent utility components (ESDUCs), and evolutionary perfect Bayesian equilibrium (EPBE). Using a simple extensive form game, we illustrate the efficiency-enhancing role of a powerful ESDUC, the vengeance motive. Incorporating behavioral noise and observational noise leads to a range of (short run) Perfect Bayesian equilibria (PBE) involving both vengeful and non-vengeful types. We then derive two (long run) EPBE, one where both types survive and reap mutual gains, and a second where only the non-vengeful type survives and there are no mutual gains.
Keywords: B52; C73; D64; Z13; 330; negative reciprocity; perfect Bayesian equilibrium; evolutionary perfect Bayesian equilibrium; emotional state dependent utility